The Social Disutility of Software Ownership. - Douglas, David (Science & Engineering Ethics, 2011)
Software ownership allows the owner to restrict the distribution of software and to prevent others from reading the software's source code and building upon it. However, free software is released to users under software licenses that give them the right to read the source code, modify it, reuse it, and distribute the software to others. Proponents of free software such as Richard M. Stallman and Eben Moglen argue that the social disutility of software ownership is a sufficient justification for prohibiting it. This social disutility includes the social instability of disregarding laws and agreements covering software use and distribution, inequality of software access, and the inability to help others by sharing software with them. Here I consider these and other social disutility claims against withholding specific software rights from users, in particular, the rights to read the source code, duplicate, distribute, modify, imitate, and reuse portions of the software within new programs. I find that generally while withholding these rights from software users does cause some degree of social disutility, only the rights to duplicate, modify and imitate cannot legitimately be denied to users on this basis. The social disutility of withholding the rights to distribute the software, read its source code and reuse portions of it in new programs is insufficient to prohibit software owners from denying them to users. A compromise between the software owner and user can minimise the social disutility of withholding these particular rights from users. However, the social disutility caused by software patents is sufficient for rejecting such patents as they restrict the methods of reducing social disutility possible with other forms of software ownership.